2003
DOI: 10.1002/mabi.200300052
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of β‐Cyclodextrin Based Functional Monomers and its Copolymers with N‐isopropylacrylamide

Abstract: Two novel monovinyl β‐cyclodextrin (β‐CD) monomers are synthesized. Their chemical compositions are characterized by means of element analysis, NMR and FT‐IR spectroscopy. The results show that the synthesis techniques used are convenient and efficient. Using N‐isopropylacrylamide as a comonomer, two novel linear copolymers can also be synthesized.Synthesis route of monovinyl β‐CD monomers.magnified imageSynthesis route of monovinyl β‐CD monomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
104
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(106 citation statements)
references
References 14 publications
2
104
0
Order By: Relevance
“…Subsequently, the carboxylic acid-functionalized tubes were activated with SOCl 2 followed by treatment with HDA-β-CD, yielding SWCNTs-β-CD. The introduction of β-CD on the surface of SWCNTs was proved by the appearance of an -C-O-C-stretch at 1030 cm -1 , -CONH-stretch at 1550 cm -1 as well as -CH 2 -stretch at 2987 cm -1 in the FTIR spectrum ( Figure 1C) [39].…”
Section: Preparation Of β-Cd Covalently Functionalized Swcnts (Swcntsmentioning
confidence: 95%
See 1 more Smart Citation
“…Subsequently, the carboxylic acid-functionalized tubes were activated with SOCl 2 followed by treatment with HDA-β-CD, yielding SWCNTs-β-CD. The introduction of β-CD on the surface of SWCNTs was proved by the appearance of an -C-O-C-stretch at 1030 cm -1 , -CONH-stretch at 1550 cm -1 as well as -CH 2 -stretch at 2987 cm -1 in the FTIR spectrum ( Figure 1C) [39].…”
Section: Preparation Of β-Cd Covalently Functionalized Swcnts (Swcntsmentioning
confidence: 95%
“…The resulting white precipitate was recrystallized from deionized water and dried under vacuum. 1 The preparation of HDA-β-CD was performed as described by Liu, et al [39]. In a typical experiment, 5.0 g of Mono-6-OTs-β-CD (3.8 mmol) and 10.0 g (0.17 mol) of HAD were charged into a bottom flask equipped with a condenser.…”
Section: Preparation Of Mono-6-(hexanediamino)-β-cy-clodextrin (Hda-βmentioning
confidence: 99%
“…As shown in Table III, the samples A, B, and C was prepared using the same molar ratio (b-CD : AAc ¼ 1 : 10) at different reaction temperatures for 37 h. The results indicate that their ratios of T % 1718 /T % 2938 increase with the increase in temperature, because there exists a marked variation for ratios of T % 1718 /T % 2938 at 30-40 C compared to the ratios at [20][21][22][23][24][25][26][27][28][29][30] C. In addition, it is found that, within 7-37 hours, the ratios of T % 1718 / T % 2938 for samples D, E, F, and B increase gradually with the increase in reaction time, wheseas the ratios of T % 1718 /T % 2938 for samples G, H, F, and I increase following the increase in the molar ratio of b-CD and AAc.…”
mentioning
confidence: 91%
“…17 The latter preparation method allows easy incorporation of functional groups within the polymer chain by simple copolymerization. 18 Our group has recently focused on the synthesis of water-soluble copolymers containing ␤-CD side chains and crosslinked ␤-CD materials through the free radical copolymerization of a new ␤-CD monomer, 2-hydroxy-3-methacryloyloxypropyl ␤-CD (␤W7 MAHP), which was developed by Wacker Chemie GmbH and consists of methacryloyl moieties grafted to a 2-hydroxypropyl ␤-CD derivative. 19 In a previous work, the characterization of this ␤W7 MAHP monomer by a matrix-assisted laser desorption/ionization time of flight mass spectrometry analysis demonstrated that ␤W7 MAHP is a complex mixture including at least 60 identified isomers.…”
Section: Introductionmentioning
confidence: 99%